UK recommendations for SDHA germline genetic testing and surveillance in clinical practice. Issue 2 (8th March 2022) - Hanson, Helen; Durkie, Miranda; Lalloo, Fiona; Izatt, Louise; McVeigh, Terri P; Cook, Jackie A; Brewer, Carole; Drummond, James; Butler, Samantha; Cranston, Treena; Casey, Ruth; Tan, Tricia; et al.
Abstract : SDHA pathogenic germline variants (PGVs) are identified in up to 10% of patients with paraganglioma and phaeochromocytoma and up to 30% with wild-type gastrointestinal stromal tumours. Most SDHA PGV carriers present with an apparently sporadic tumour, but often the pathogenic variant has been inherited from parent who has the variant, but has not developed any clinical features. Studies of SDHA PGV carriers suggest that lifetime penetrance for SDHA-associated tumours is low, particularly when identified outside the context of a family history. Current recommended surveillance for SDHA PGV carriers follows an intensive protocol. With increasing implementation of tumour and germline large panel and whole-genome sequencing, it is likely more SDHA PGV carriers will be identified in patients with tumours not strongly associated with SDHA, or outside the context of a strong family history. This creates a complex situation about what to recommend in clinical practice considering low penetrance for tumour development, surveillance burden and patient anxiety. An expert SDHA working group was formed to discuss and consider this situation. This paper outlines the recommendations from this working group for testing and management of SDHA PGV carriers in clinical practice.